Pengaruh Influencer dan Inovasi Produk terhadap Keputusan Pembelian Produk Virtual dalam Mobile Legend - Febrianto, Dani; Siregar, Salim (Peneliti.net, 2025)
This study aims to analyze the influence of influencers and product innovation on purchasing decisions for virtual products in the Mobile Legends game, with a case study of the Mobile Legend Universe Discord community. The study used quantitative methods with a multiple regression analysis approach to test the relationship between the independent variables (influencers and product innovation) and the dependent variable (purchase decision). The results showed that influencers have a positive influence of 35.6% on purchasing decisions, with the main indicators being reputation and information updates submitted by influencers. Meanwhile, product innovation exerts a greater influence, at 50.4%, mainly through affordable product prices and product revisions that improve user experience. Simultaneously, these two variables influence purchase decisions by 54.4%, while the other 46.2% is influenced by other factors not explained in this study. These findings underscore the importance of influencer-based marketing strategies and product innovation in increasing player interest in and loyalty to in-game virtual products.